Melting and sublimation of graphene and silicene - Юрий Дмитриевич Фомин; Елена Николаевна Циок; Валентин Николаевич Рыжов (Physics of Complex Systems)
This study involves molecular dynamics simulations aimed at investigating the crystal structure collapse of graphene, graphite and silicene. It shows that in the case of graphene and graphite, crystal structure collapse is related to the sublimation of the sample. At the same time, when a silicene sample is heated at constant volume, it comes into the liquid–gas two-phase region of the phase diagram. The difference in the crystal structure collapse of graphene and silicene is caused by the differences in the pressure of the liquid–gas–crystal triple point.